KONTRIBUSI PESANTREN DALAM REHABILITASI PECANDU NARKOBA (Studi Kasus di Pondok Pesantren Darun Najah Dawuhan Kidul Papar Kediri) - Abdur Rohman; Siswo (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2020)
Islamic boarding schools have a great kindness to this nation. Starting from the struggle to fight off the colonizers to the socio-political sphere. An example regarding contribution of Islamic boarding school in the social sphere is to become a partner of state in the rehabilitation of drug addicts. One of the Islamic boarding schools that contribute to rehabilitating drug addicts is the Darun Najah boarding school in Dawuhan Kidul, Papar, Kediri, East Java. This Islamic boarding school was made choice by BNN Kediri as a partner because it gave evidence to cure drug addicts with a relatively short time. This research concludes that the causes of people becoming drug addicts start from a free drug but it is rejected due to forbidden good, then; second, it appears curiosity and he wants to try when getting problems; third, he is addicted and forced to buy; fourth, he justifies all of ways to obtain the forbidden goods; fifth, hegashes himself and even others. While the characteristics of marijuana addict in cigarettes is to have a smell like burning rubber; the characteristic of a methamphetamine addict is laughing to himself without being funny; their situation is often confused, blank, digressing when he speaks and likes a flu. The rehabilitation process of drug addicts in Darun Najah Islamic boarding school is to combine herbal and spiritual medicine models. Herbal medicines consist of honey, olive oil and kangkung leaves. While spiritual medicines are the prayer activities in midnight, the study of classic book, prayers and having asma’ water and gurah.